Las actividades antropogénicas y la calidad del agua del río Jipijapa Manabí Ecuador - Arteaga Mendoza, Gema Gabriela (2019)
The relationship between the anthropogenic activities and the water quality of the Jipijapa River in the city of the same name in Manabí province was evaluated. Using the method of observation and interview technique, anthropogenic activities water demand, washing clothes and other items, car and other automotive washing, personal hygiene, animal grooming, stone materials procurement, recreation, discharge of solid waste discharge of domestic liquid waste and dumping of agricultural and industrial liquid waste, referred to the object under study and; applying the methods and techniques of standard analysis, the river water was characterized, for the calculation of its quality, through the ICAGUA indicator, with the inclusion of parameters like aspect, pH, dissolved oxygen, electrical conductivity, hardness, total dissolved solids, fats and oils, ammonia nitrogen, nitrates, sulfates, phosphates, BOD5, detergents, total pesticides and total coliforms. The idea about the mentioned activities negatively influence the water quality of the river under study, was defended. According to the results, the anthropogenic activities most practiced and with greater incidence in the water of the river, were washing of clothes and other articles, dumping of solid waste (67% of sample agreed on it), spillage of domestic liquid waste and, dumping of agricultural and industrial liquid waste. Regarding the weighting of the water quality of the river, carried out by means of the ICAGUA index, with 15 pollution indicator parameters, the results averaged 29,15% at the entrance of the river in the city and 16,74% at the output, which implied percentages of quality reduction between 36 and 48% and poor water quality. The relationship between the variables can be expressed based on the results of the hypothesis tests, which showed high significance (99,5% confidence) when accepting that the anthropogenic activities practiced along the route of the water flow through the city, they, negatively influence the quality of their waters.